1994
DOI: 10.1073/pnas.91.26.12487
|View full text |Cite
|
Sign up to set email alerts
|

Identification of synaptic proteins and their isoform mRNAs in compartments of pancreatic endocrine cells.

Abstract: Several proteins that are of importance for membrane trafficking in the nerve terminal have recently been characterized. We have used Western blot and immunohistochemistry to show that synaptotagmin, synaptobrevin/VAMP (vesicle-associated membrane protein), SNAP-25 (synaptosomal-associated protein of 25 kDa), and syntaxin proteins are present in cells of the islets of Langerhans in the endocrine pancreas. Synaptotagmin-like immunoreactivity (-LI) was localized to granules within the cytoplasm of a few endocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
120
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(141 citation statements)
references
References 30 publications
16
120
0
1
Order By: Relevance
“…Based on our protein quantification of SNARE complexes, we suggest that transition from the syntaxin1/SNAP-25 heterodimer to the ternary SNARE complex simply requires engagement of synaptobrevin. The localization of syntaxin1 and SNAP-25 on the chromaffin cell plasma membrane, in the absence of synaptobrevin, agrees well with the SNARE distribution in neurons and pancreatic secretory cells (15,25). The segregation of secretory granules from the plasma membrane, in chromaffin cells, is thought to be due to the cortical actin network (13,26).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Based on our protein quantification of SNARE complexes, we suggest that transition from the syntaxin1/SNAP-25 heterodimer to the ternary SNARE complex simply requires engagement of synaptobrevin. The localization of syntaxin1 and SNAP-25 on the chromaffin cell plasma membrane, in the absence of synaptobrevin, agrees well with the SNARE distribution in neurons and pancreatic secretory cells (15,25). The segregation of secretory granules from the plasma membrane, in chromaffin cells, is thought to be due to the cortical actin network (13,26).…”
Section: Discussionsupporting
confidence: 66%
“…In particular, studies of the three neuronal SNARE proteins, synaptobrevin2 from secretory vesicles and the plasma membrane syntaxin1 and SNAP-25, contributed significantly to our understanding of the last step of vesicle exocytosis. These three proteins are also involved in exocytosis from many endocrine cells throughout the body, including adrenaline-secreting chromaffin cells and insulin-secreting pancreatic ␤-cells (13,15). It is now generally accepted that the three SNARE proteins form a parallel four-helix bundle that can drive the fusion of two apposing membranes (3).…”
Section: Discussionmentioning
confidence: 99%
“…First, syntaxin 4 was reported previously not to be involved in the regulation of insulin secretion based upon the overexpression of the full-length syntaxin 4 protein (14,30,31). However, the full-length syntaxin 4 protein does not function as a dominant-interfering mutant in other cell systems, and currently, there are no specific endotoxins for the syntaxin 4 isoform.…”
Section: Discussionmentioning
confidence: 99%
“…These components, including N-ethylmaleimide-sensitive factor (NSF), soluble NSF attachment protein (SNAP), and membrane-associated SNAP receptors (SNAREs) such as syntaxin-1 and SNAP-25, are also expressed in pancreatic beta cells [3,4,5], which play an important role in insulin exocytosis [6,7,8,9]. We [10] and others [11,12] have demonstrated that the expression of SNARE proteins is decreased in diabetic animal models.…”
Section: Introductionmentioning
confidence: 97%